2021
DOI: 10.1109/mic.2021.3051675
|View full text |Cite
|
Sign up to set email alerts
|

Security and Privacy in IoT Smart Healthcare

Abstract: Patient care is a key element of healthcare practices. The use of Healthcare IoT could enhance the lives of patients and the quality of services provided by medical practitioners, nurses, clinicians, pharmaceutical companies and government in general. Wireless healthcare monitoring systems tremendously used in hospitals and other healthcare practices and witnessed as a revolution in the medical field. Nevertheless, security and privacy for interconnected things are mostly overlooked on the Internet of Things p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In Ref. [19], a systematic approach has been followed to report that the current issues with WBSN include the fact that the data gathered through sensors is poorly managed, and a lack of strategy is observed. For that, the study has suggested the use of homomorphic encryption.…”
Section: Related Work On Wbanmentioning
confidence: 99%
“…In Ref. [19], a systematic approach has been followed to report that the current issues with WBSN include the fact that the data gathered through sensors is poorly managed, and a lack of strategy is observed. For that, the study has suggested the use of homomorphic encryption.…”
Section: Related Work On Wbanmentioning
confidence: 99%
“…When employed for accurate health diagnosis, sensor nodes that communicate data to the medicine server (MS) via the base station (BS) provide privacy and security risks to users [18]. e security and privacy of IoT in healthcare and issues with developing security standards, including security and privacy alternatives, are all covered in this article [19]. Homomorphic encryption allows computation on encrypted data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proper usage of the IoT can help overcome different medical challenges, such as speed, price, and complexity [ 6 , 7 ]. The IoT can easily be customized to monitor individual patients' vital signs and the treatment of COVID-19 patients [ 8 , 9 ]. The overall performance of healthcare can be improved via a digitally controlled health management system during an emergency such as the COVID-19 pandemic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%